Concept of Human Resources Development to Improve Teacher Performance: Multi-Case Study - Muh Burhanudin Harahap; Maria Veronika Roesminingsih; Mudjito Mudjito (Indonesia Approach Education, 2020)
This study aims to analyze the concept of Human Resource Development carried out by schools in improving the performance of teaching staff at Elementary School Muhammadiyah of 1 Jember and Al Baitul Amien of 1 Jember. This research method uses a qualitative approach with a multi-case study design. The multi-case study used in this study uses two research sites. Data collection techniques in this study used participant observation, documentation, and interviews. Based on the research conducted, it can be concluded that the concept of the human resource development program carried out by these schools to improve the quality of teacher performance, namely: (1) increasing the abilities, skills, attitudes, and responsibilities of educators (teachers) to be more effective and efficient, (2) optimizing human resource development as much as possible by delegating to educators (teachers), and (3) striving to improve education quality by recommending educators (teachers) to take further studies to a higher level. There is no multi-case study research in improving the performance of students.